Heuristic Evaluation on Barcode Scanner Mobile Application for Halal Food Product in Malaysia - Prasetijo, Bimo Kuncoro Yakti; Zairien Natasa binti Zaini; Farra Aliesya binti Ameran; Hazwani binti Rahmat (Multidisciplinary Applied Research and Innovation, 2022)
Conventional barcode scanner shows the price of the item without any detailed description. The primary issue is the usage of fake Halal logos among product manufacturers that has caused a major concern among Muslim consumers. Consequently, consumers become skeptical in purchasing food and related products. Hence, this study made an attempt in developing a “Halal Food Product Barcode Scanner” application based on the waterfall methodology. Heuristic evaluation has been conducted to evaluate the usability of the application. The result indicates that the application works flawlessly in some heuristic aspect although some minor usability issues are still present which does not impair the overall experience when using the application.